Evolving racial/ethnic disparities in AML survival in the novel therapy era - Xin Wang; Phyllis A. Gimotty; Andrew H. Matthews; Ronac Mamtani; Selina M. Luger; Elizabeth O. Hexner; Daria V. Babushok; Shannon R. McCurdy; Noelle V. Frey; Ximena Jordan Bruno; Saar Gill; Mary Ellen Martin; et al. (Blood Advances)
Abstract: Little is known about the impact of recent advances in acute myeloid leukemia (AML) treatment on racial/ethnic disparities in survival outcomes. We performed a retrospective cohort study of patients with newly diagnosed AML using data from a nationwide electronic health record–derived deidentified database. Patients were categorized based on their diagnosis date relative to venetoclax approval, as pre–novel therapy era (Pre era; 2014-2018; n = 2998) or post–novel therapy era (Post era; 2019-2022; n = 2098). Patients in the Post era were older and had more comorbidities than Pre era. Non-Hispanic Black (NHB) and Hispanic patients were younger and more likely to have lower socioeconomic status than non-Hispanic White (NHW) patients, with no differences in the distributions of key disease features. After accounting for age and comorbidity, overall survival (OS) was higher in patients in Post era than Pre era (adjusted hazard ratio [aHR], 0.90; 95% confidence interval [CI], 0.83-0.96). In Pre era, NHB had a 22% higher hazard of death than NHW (aHR, 1.22; 95% CI, 1.04-1.43), whereas worse OS was not observed for NHB in Post era (aHR, 0.86; 95% CI, 0.69-1.08; predicted 2-year survival, 45.3% vs 39.9%). Utilization of novel therapeutics in frontline therapy did not differ by race/ethnicity. Among patients receiving venetoclax-based induction, particularly those without TP53, RAS, or FLT3-ITD mutations, results suggested higher OS for NHB than NHW patients (aHR, 0.67; 95% CI, 0.45-1.01). Additional studies are needed to elucidate factors contributing to these observed survival differences and to inform strategies to optimize outcomes for all patients with AML.